The Relationship between Internet Advertisement Value and Customer Buying Behavior in Kluang - Lau Swee Hui; Mohd Zarir Yusoff (Research in Management of Technology and Business, 2023)
It is widely acknowledged that the most useful source of information when making purchasing decisions is advertisement. There are a variety of advertisement values that influence customer buying behavior. This study also focuses on existing effects like incentives and personalization, which have a lot to do with internet advertisement, but there hasn’t been a lot of work done to draw conclusions from it. Consequently, the main purpose of this research is identify the level of the customer buying behavior, as well as the level of internet advertisement value that influences customer buying behavior in Kluang, Johor, as well as to evaluate the relationship between the internet advertisement value and customer buying behavior in Kluang. This research was conducted in Kluang, Johor. The targeted number of respondents in this study are 384 people, and the data is gathered using a questionnaire and will be quantitatively evaluated using the SPSS software. The researcher used descriptive analysis to accomplish the first and second objectives, and the spearman rho correlation to accomplish the third. According to the study’s findings, most of the respondents of Kluang, Johor prefer to buying online from the social media because it is convenient for them, and the main factor of internet advertisement value that influences customer buying behavior is informativeness. Future researchers could benefit from a larger sample size to obtain more reliable study data, as well as a mix-method approach that combines qualitative and quantitative approaches. Consequently, it is hoped that this study will provide more information and understanding about customer buying behavior that is influenced by the value of internet advertisement.